Incommensurable histories of human experimentation and bioethics - Polšek, Darko (Array, 2008)
Histories of medicine and of bioethics are usually written jointly. Their authors mostly think that they are complementary, whereas history of bioethics is either treated as a post-hoc reaction to the history of medicine proper, or else, as a legitimate part of medical history. In such reviews, it seems that medical progress and progress of bioethics go hand in hand. But, on closer inspection neither of these claims is true. First, although bioethics seems to be of a rather recent descent, it relies on ethical and philosophical principles which have not changed drastically throughout history, so it did not "progress" purely in reaction to serendipities of medical experimentation. Also, even more pragmatic ethical regulations, for instance, a regulation that drugs should be tried on animals before they are tried on humans, existed at least since the age of Galen. But secondly, and more importantly, multiple episodes of medical history testify that medicine mostly progressed in spite of bioethical limitations, so bioethics could not have been a pure reaction to the "real thing". For example, even after the establishment of Nuernberg Code, Helsinki Declaration or Belmont Report, many physicians and countries have experimented on humans, sponsored or cooperated on projects which were, from bioethical standpoints, rather dubious. Even today, when almost all hospitals have their own Review Boards, progress of medicine is achieved in procedures which contradict basic bioethical principles given in these documents, and pharmaceutical companies experiment on people, but this time in countries where such bioethical principles have not been framed within jurisprudential guidelines. The purpose of this paper is to present landmark events and follow parallel, but "incommensurable" histories of bioethics and medical experimentation. The real question which arises from the research of these incompatible histories is the following: if the progress of medicine was followed by the multitude of bioethical limitations, how could medicine bring about such a drastic progress? And further, from a normative point of view, if we accept that bioethics serves as brakes from irresponsible experimenting of humans, can we expect such drastic progress of medicine to continue? A short answer to these questions is that the progress of medicine (and genetics), will proceed by finding holes in bioethical norms, or by adjusting bioethical standards to new precedents.